Itineraria Anatolica Antiqua. La red viaria de los sectores montañosos septentrionales de Anatolia: las rutas nororientales y el Imperio hitita - González Salazar, Juan Manuel; Lucía Castejón, Rodrigo (Gerión. Revista de Historia Antigua, 2009)
The investigation of a particular region also bears the study of its net of communications. So, in the following pages, it will be briefly checked the routes and itineraries that could cross the complicated landscape of great part of north Anatolia during the Antiquity with the intention of doing a study to approach firmly to a complete regional research of this area in the Hittite Period, during great part of the II millennium B.C.
Keywords: Northern Anatolia; Hittites; Anatolian Geography; Routes; Gasgeans